Establishing schools that promote health: Is it worth doing? - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava; Jegadeesh Ramasamy (Turkish Society of Public Health Specialists, 2013)
School is a setting that plays a significant role in the physical, emotional, social and mental development of a child. Schools provide an exceptional opportunity for assisting millions of young children to acquire health supportive knowledge, values, attitudes and behaviors. The World Health Organization has launched a global school health initiative in order to establish and strengthen health promotional and educational activities at the local, national, and international levels for ensuring an improvement in the health of students, school personnel, families and other members of the community. The ultimate aim of this initiative is to enhance the number of "Health-Promoting Schools". A health promoting school is the one that continually strengthens its capacities as a healthy institute in living, learning and working. Various types of barrier, such as the unavailability of all components of school health services within the school premises, a lack of clear instructions and overlapping roles of different agencies involved,logistic concerns, parents' and teachers' reservations about the competence of healthcare personnel and the quality of services; lack of effective communication between nurses and physician have been recognized as relevant to  the global effort for increasing the number of health promoting schools worldwide. In view of the wide range of benefits associated with school health services, different strategies have been suggested to ensure a maximum coverage. The first and foremost priority is to develop national guidelines establishing the scope and range of services offered under the umbrella of school health services. Subsequently other measures that can be implemented in a time-bound phased manner to cover the entire country  include the following: ensuring the  availability of physicians and nurses, establishing  alliances with different national and international agencies, addressing identified barriers and promoting  research work to improveand widen the services based on the children's health needs. It is concuded that schools promoting health provide a realistic and effective initiative under the global school health initiative for extending the healthy behavior of students, their families and the community. Keywords: School, Nurses, health education, World Health Organization